2021
DOI: 10.1007/s00107-021-01667-5
|View full text |Cite
|
Sign up to set email alerts
|

Generalized cutting force model for peripheral milling of wood, based on the effect of density, uncut chip cross section, grain orientation and tool helix angle

Abstract: The influence of the grain angle on the cutting force when milling wood is not yet detailed, apart from particular cases (end-grain, parallel to the grain, or in some rare cases 45°-cut). Thus, setting-up wood machining operations with complex paths still relies mainly on the experience of the operators because of the lack of scientific knowledge easily transferable to the industry. The aim of the present work is to propose an empirical model based on specific cutting coefficients for the assessment of cutting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…The effect of cutting condition on the qualitative and quantitative parameters of strain field near the cutting edge was studied in a greater detail. The FA affected primarily the quantitative parameters, which is in agreement with Curti et al (2021). The increasing FA increased the both tension and compression strain magnitude in the same manner for hardwood and softwood.…”
Section: Resultssupporting
confidence: 84%
“…The effect of cutting condition on the qualitative and quantitative parameters of strain field near the cutting edge was studied in a greater detail. The FA affected primarily the quantitative parameters, which is in agreement with Curti et al (2021). The increasing FA increased the both tension and compression strain magnitude in the same manner for hardwood and softwood.…”
Section: Resultssupporting
confidence: 84%
“…Some studies have shown that, in wood material processing, cutting tools and cutting parameters have a decisive effect on the surface quality [7,8]. No matter whether one is milling soft or solid wood, it has been found that the cutting angle, feed speed, wood fiber orientation angle, and milling depth that are used have significant influences on the cutting force, chip formation, and surface quality [9,10]. As a typical soft wood, Paulownia requires fundamental investigation into its machinability due to the currently lack of information surrounding it in the literature.…”
Section: Introductionmentioning
confidence: 99%